Short and Long-Term Performance of Eco-Efficient Concrete Mixtures - Tagliaferri de Grazia, Mayra (Université d'Ottawa / University of Ottawa, 2023)
Concrete is the most widely used construction material worldwide, yet, it presents major sustainability drawbacks due to the CO2 released during the manufacturing of its main constituent, cement. Several approaches are used to improve concrete’s eco-efficiency and reduce the binder intensity index, a metric used to measure the eco-efficiency of concrete, to a value below that of conventional concrete mixtures (i.e., 10 kg/m3.MPa-1 for 25-40 MPa mixtures). Particle Packing Models (PPM) is consequently an approach that can be used to enhance system packing density, reducing cement content while increasing hardened state properties and durability (i.e., reducing porosity). However, packed mixtures normally present issues in the fresh state while their hardened state performance is not fully comprehended. Therefore, this Ph.D. project proposes a new mix-design method called PPM-MP approach to develop eco-efficient mixtures. First, a detailed laboratory investigation was conducted on mixtures developed using the proposed approach in order to understand their fresh and hardened state performance. Concrete samples containing distinct ranges of cement content (320, 250, 200, 150 kg/m3) and slump (180, 90, and 20 +/- 20 mm) were fabricated and a wide range of fresh state tests (pH, temperature, fresh density, air content, slump and rheology over time) and hardened state tests (apparent porosity, surface electrical resistivity, compressive strength, and modulus of elasticity) were performed over time. Then, its performance against the alkali-silica reaction (ASR) induced expansion and deterioration, which is one of the leading and most damaging distress mechanisms issues in durability, was evaluated. In this section of the project, four sustainable concrete mixtures developed with varying cement content (e.g., 325, 250, 200, and 150 kg/m3) were developed and compared to a control mixture containing 420 kg/m3 of cement content. The mixtures were tested over a year under Concrete prism test (CPT) setup, which is the current method used to evaluate concrete ASR and using three different non-boosted test setups (i.e., Wrapped - W, Soaked - S, and Encapsulated - E). Moreover, two distinct types of highly reactive aggregates (e.g., Springhill Greywacke coarse aggregate and Texas Polymictic sand) were selected. Microscopic analysis was used to better understand the impact of ASR on sustainable mixtures, as well as the differences in ASR-damage and crack propagation under different test protocols. The results show the feasibility of producing an eco-efficient mixture in a more efficient manner which may contribute to the Net Zero Concrete targets. The proposed PPM-MP approach improves the sustainability of concrete mixtures and can be used for specific projects requiring 28-day compressive strength ranging from 18 to 45 MPa and slumps (180, 90, and 20 +/- 20 mm).
Keywords: eco-efficient concrete; rheology; low cement content; particle packing models; mobility parameters; durability and long-term performance; alkali-aggregate reaction (ASR); alkali-aggregate reaction (ASR); microscopic characterization; crack propagation; damage rating index (DRI)